Tinjauan Yuridis terhadap Faktor Penyebab Perceraian di Pengadilan Agama Purwodadi - Mahdaniyal Hasanah Nuriyyatiningrum (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2019)
Married life is very likely to occur a misunderstanding between husband and wife. The situation can sometimes be overcome peacefully, but sometimes the efforts for peace that actually lead to hatred and lead to disputes between the two, even between the two sides of the family. If the marriage continues, then the basic goals of the household will not be achieved. In Islam, divorce is an act that is hated by Allah, but it is permissible. Purwodadi Religious Court is a class IA court. Grobokan Regency occupies the second place in terms of divorce in Central Java, with the number of divorces reaching three thousand. The stereotype of